2013
DOI: 10.1016/j.str.2013.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for Autoactivation of Human Mst2 Kinase and Its Regulation by RASSF5

Abstract: SUMMARY The tumor-suppressive Hippo pathway controls tissue homeostasis through balancing cell proliferation and apoptosis. Activation of the kinases Mst1/2 is a key upstream event in this pathway and remains poorly understood. Mst1/2 and their critical regulators RASSFs contain SARAH domains that can homo- and hetero-dimerize. Here, we report the crystal structures of human Mst2 alone and bound to RASSF5. Mst2 undergoes activation through trans-autophosphorylation at its activation loop, which requires SARAH-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
136
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(148 citation statements)
references
References 49 publications
6
136
0
6
Order By: Relevance
“…To characterize potential structural differences between active and inactive Mst2, we analyzed 15 N-labeled human wild-type Mst2 and kinase-inactive Mst2 D146N proteins with nuclear magnetic resonance (NMR) spectroscopy. We showed previously that the linker region of human Mst2 is flexible (Ni et al 2013). Strikingly, we observed a new cluster of peaks a ∼8.5-9.0 ppm in the spectrum of Mst2…”
Section: Mst2 Autophosphorylates Its Linker To Create Phospho-dockingsupporting
confidence: 50%
See 2 more Smart Citations
“…To characterize potential structural differences between active and inactive Mst2, we analyzed 15 N-labeled human wild-type Mst2 and kinase-inactive Mst2 D146N proteins with nuclear magnetic resonance (NMR) spectroscopy. We showed previously that the linker region of human Mst2 is flexible (Ni et al 2013). Strikingly, we observed a new cluster of peaks a ∼8.5-9.0 ppm in the spectrum of Mst2…”
Section: Mst2 Autophosphorylates Its Linker To Create Phospho-dockingsupporting
confidence: 50%
“…Lats1C ΔHM and Lats1C were further purified by a Mono S cation exchange column followed by a Superdex 200 gel filtration column (GE Healthcare). The expression and purification of Mst2 WT , Mst2 D146N , Mst2 ΔL , and Mst2 KD were described previously (Ni et al 2013). The pMst2-Mob1 complex was obtained by mixing 30 mg/mL Mob1 ΔN50 with the pMst2 MBM peptide (DEEEED GpTMKRNATSPQVQRPSFMDYFDKQ) at 1:2 molar ratio.…”
Section: Protein Expression and Purificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, it is evident that RASSFs disrupt MST1/2 dimerization and prevent their autophosphorylation. However, interaction of RASSFs with already activated MST1/2 may prevent MST1/2 dephosphorylation and therefore sustain MST1/2 kinase activity (Guo et al 2011;Ni et al 2013).…”
Section: The Regulation Of Lats-activating Kinases Mst1/2 and Map4ksmentioning
confidence: 99%
“…4A and 6A). It has been reported that RASSF5 enables the HIPPO pathway (via MST2/ STK3) to respond to and integrate diverse cellular signals by acting as a positive regulator of MST2/STK3 (35). A recent study revealed a role of YAP, the central effector of the HIPPO pathway during HSC activation (13); thus, we analyzed whether ERAS activates the HIPPO pathway, which may lead to phosphorylation and proteolytic degradation of YAP (supplemental Figs.…”
Section: ⌬N/s/smentioning
confidence: 99%